An experimental study of the longitudinal aerodynamic and static stability characteristics of hang gliders - Kilkenny, E. A. (Cranfield University, 1986)
A mobile experimental test facility has been developed to carry out the aerodynamic evaluation of hang glider wings normally performed in a wind tunnel. Longitudinal aerodynamic data obtained using this facility is presented for three modern hang glider wings, a Silhouette, Demon 175 and Magic 166, together with surface flow patterns for the latter two wings. The longitudinal stability criterion are studied and alternatives established, equivalent to the stick fixed and stick free criterion for conventional aircraft, relevant to weight shift controlled wings. These are based on the pilot's position and control force to trim. The aerodynamic data obtained from the mobile facility is used to calculate these parameters and the longitudinal static stability of each wing is examined. The influence of several rigging parameters, variable by the pilot before flight, on the longitudinal static stability and control of the hang glider are also investigated.